Risk factors of soil-transmitted helminth infection among elementary school students - Kadek Adit Wiryadana; I Wayan Ardyan Sudharta Putra; Putu Diah Saraswati Rahayu; Made Martha Pradnyana; Made Lady Adelaida; I Made Sudarmaja (Indonesian Pediatric Society, 2017)
Background Helminth infection remains a health problem, especially in school-aged children. Mass eradication programs with a single dose of anti-helminthic drugs were employed by the local government in some endemic areas in Bali. However, the effectiveness of the programs has not been well evaluated. Objective To investigate prevalence and possible risk factors of helminth infection, including nutritional status, in elementary school students from endemic areas who participated in mass eradication programs. Methods This cross-sectional study involved 126 students from Elementary School No. 3 Gegelang, Karangasem, Bali, a location that had recently undergone a mass eradication program. Diagnoses were based on direct smear examination of fecal specimens. Information on suspected risk factors and nutritional status were collected by questionnaire and anthropometric measurement, respectively. Statistical analyses included Chi-square and odds ratio, using SPSS v21 software. Results The prevalence of helminth infection was 31.7% with etiologies of Trichuris trichuria (75%), Ascaris lumbricoides (17.5%), or both infections (7.5%). Habits of not using footwear [OR=4.88; 95%CI 1.15 to 20.65], not keeping nails trimmed [OR=3.33; 95%CI 1.07 to 10.37], and absence of a proper toilet [OR=4.31; 95%CI 1.93 to 9.64] were found to be significant risk factors for helminth infection. However, we found no significant association between helminth infection and nutritional status, although a considerable number of students had less than normal reference values, in terms of weight, height, and BMI for age. Conclusion The prevalence of helminth infection continues to be high, with personal hygiene and sanitation as significant risk factors. History of mass eradication programs did not confer an effective protection against helminth infection.